Informativeness of biomechanical criteria in assessing the competitive efficiency of highly qualified cross-country skiers - Novikova, N. B.; Ivanova, I. G.; Beleva, A. N. (Theory and Practice of Physical Culture, 2024)
Objective of the study was to assessment of the influence of competitive conditions on the biomechanical characteristics of the technique of simultaneous single-step skating skiing (SSS).